Optimization Of ZIS Fund Distribution Management At (BAZNAS) - Sulaiman Efendi; Dina Chairunnisa (ZAWA: Management of Zakat and Waqf Journal, 2021)
Zakat, Infaq, Sadaqah (ZIS) has great potential in the economy and development of the ummah. Optimal management of ZIS funds can provide positive contributions both in economic development and in the construction of places of worship, especially for Muslims. BAZNAS as an institution that manages zakat, infaq and shodaqah funds has a very strong role and function to be able to utilize zakat, infaq, shodaqah funds in empowering the ummat / economy and building places of worship. Analysis of strengths, weaknesses, opportunities, threats is important so that BAZNAS can continue to exist in carrying out its function in serving the community and of course it can run in accordance with the applicable laws in Islam. In order to function optimally in terms of collection and distribution as well as efficiency in the use of ZIS funds are things that must be fully considered. The distribution of ZIS must also be optimized, namely the construction / renovation of places of worship both in rural areas / around cities so that people do not demand alms / infaq / zakat in the middle of the road for the construction of places of worship. Optimization of ZIS management, from consumptive to productive and more efficient.